The Use Of Digital Media To Improve Students’ Writing Articles In Writing Iii Courses - Yulandari, Evi Safitri (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study aims to investigate the effect of using digital media in writing articles in writing III courses. The design used in this study was a descriptive qualitative analysis and the method in this study is used to analyze descriptions or descriptions systematically about the use of digital media to improve students' Writing articles, this study illustrates that digital media has a positive impact on students' writing skills. The results of the study indicate that fast access to information through online platforms, increased creativity through digital writing tools, and interaction with readers through social media can improve the quality of articles produced by students. However, challenges related to the selection and verification of information were also found, emphasizing the need for media literacy development. In addition, this study contributes to the understanding of how digital media can support writing III Course learning and offers a foundation for developing a curriculum that is responsive to technological developments. So that digital media used to deliver material can take place effectively to improve students' literacy in learning so that it can run according to educational goals.